Investigation of Relationship between Intellectual Capital and Social Responsibility with Ethical Behavior of Faculty Members - Jamshid Bahmaei; Rita Rezaee; Mohamad Khavasi; Rana Hamedpour (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: Intellectual capital is the key factor in value creation for organizations. Social responsibility means taking some measures for the improvement of  the community welfare beyond the interests of the organization and legal requirements. To researchers, ethical behavior in the organization means acting in ways consistent with the ethical values of the organization. In this regard, this study was conducted to determine the relationship between intellectual capital and social responsibility and its relationship with the professional ethics of faculty members of the Faculty of Medical Sciences of Abadan, Iran. Methods: This research was descriptive-correlational. The required data were collected from 78 people using census method. To this end, information was collected by researchers using intellectual capital, social responsibility, and ethical behavior questionnaires. Finally, the data were analyzed using SPSS software, Pearson correlation coefficient, and regression tests. Results: There was a positive and significant relationship between intellectual capital and all its subscales with the ethical behavior of the faculty members (P<0/05). According to the results, all components of intellectual capital were able to predict ethical behavior. Furthermore, a positive and significant relationship was found between social responsibility and all its subscales with the ethical behavior of faculty members and all components of social responsibility were able to predict ethical behavior. Conclusion: The faculty members with high intellectual capital and social responsibility will show more ethical behavior in educational and research activities. Therefore, they will improve the level of the university and the scientific community of the country.